Refined analytical pipeline for the pharmacodynamic assessment of T-cell responses to vaccine antigens - Pavlidis, Michail Angelos; Viborg, Nadia; Lausen, Mads; Rønø, Birgitte; Kleine-Kohlbrecher, Daniela (Frontiers in Immunology, 2024)
Pharmacodynamic assessment of T-cell-based cancer immunotherapies often focus on detecting rare circulating T-cell populations. The therapy-induced immune cells in blood-derived clinical samples are often present in very low frequencies and with the currently available T-cell analytical assays, amplification of the cells of interest prior to analysis is often required. Current approaches aiming to enrich antigen-specific T cells from human Peripheral Blood Mononuclear Cells (PBMCs) depend on in vitro culturing in presence of their cognate peptides and cytokines. In the present work, we improved a standard, publicly available protocol for T-cell immune analyses based on the in vitro expansion of T cells. We used PBMCs from healthy subjects and well-described viral antigens as a model system for optimizing the experimental procedures and conditions. Using the standard protocol, we first demonstrated significant enrichment of antigen-specific T cells, even when their starting frequency ex vivo was low. Importantly, this amplification occurred with high specificity, with no or neglectable enrichment of irrelevant T-cell clones being observed in the cultures. Testing of modified culturing timelines suggested that the protocol can be adjusted accordingly to allow for greater cell yield with strong preservation of the functionality of antigen-specific T cells. Overall, our work has led to the refinement of a standard protocol for in vitro stimulation of antigen-specific T cells and highlighted its reliability and reproducibility. We envision that the optimized protocol could be applied for longitudinal monitoring of rare blood-circulating T cells in scenarios with limited sample material.